The influence of seminal plasma on offspring development and health. (January 2020) - Morgan, Hannah L.; Watkins, Adam J.
Abstract: The concept that a father's wellbeing at the time of conception influences the development and long-term health of his offspring is now well established. However, the mechanisms underlying the paternal programming of offspring health are not fully defined. While sperm-mediated effects on offspring development have been investigated in detail, the significance of seminal plasma has been over-looked. Typically, the seminal plasma is viewed as a simple medium, with a main role to transport sperm into the female reproductive tract at the time of conception. However, a more sophisticated role for seminal plasma in the modulation of the maternal periconception cell-signalling, inflammatory and immunological physiology is emerging. Seminal plasma comprises a complex mix of nutrients, proteins, signalling molecules and cell-free genetic material which all interact with the endometrium to regulate gene expression, vascular remodelling, leukocyte recruitment and the priming of regulatory T cells (Tregs). These seminal plasma effects on the maternal periconception environment all act to facilitate uterine remodelling, embryo implantation and fetal development. Evidence is now emerging that poor paternal lifestyle factors such as diet, can modify these essential uterine responses, altering fetal development and ultimately long-term offspring health. The use of animal models has enhanced our understanding of the effects of seminal plasma on maternal uterine physiology, embryo development and offspring health. However, further studies are needed to define the interaction between seminal plasma components and female reproductive tissues in humans. Such studies will be central in providing better information and infertility treatments to intending parents.